1980
DOI: 10.1007/bf00441485
|View full text |Cite
|
Sign up to set email alerts
|

Mesomelic dysplasia, type langer?A homozygous state for dyschondrosteosis

Abstract: Both parents of a female infant with mesomelic dysplasia, type Langer, showed signs of dyschondrosteosis. This further observation suggests that this type of mesomelic dysplasia may be due to homozygosity for the autosomal dominant gene of dyschondrosteosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0
1

Year Published

1983
1983
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 15 publications
2
10
0
1
Order By: Relevance
“…Regarding mesomelic dwarfism of the hypoplastic ulna and fibula type two forms are described a dominant type described by Reinhardt and Pfeiffer (1967) in 10-15 members of a kindred, and mesomelic dwarfism of the hypoplastic ulna, fibula and mandible type which is auto-soma1 recessive and probably represents homozygosity for dyschondrosteosis. Two new reports of this disorder were by Fryns and Vanden Berghe (1979), and by Kunze and Klemm (1980). Achondrogenesis 11, Grebe or Brazilian type, a severe type of dwarfism characterized by various bone aplasias and hypoplasias of the distal long bones of the limbs and hypoplastic digits, first detected and described in two German sisters by Grebe (1952), a new report of this disorder was by Khan and Khan (1982) in an Andhra family which belongs to a highly endogenous group in Pradesh, India.…”
mentioning
confidence: 92%
“…Regarding mesomelic dwarfism of the hypoplastic ulna and fibula type two forms are described a dominant type described by Reinhardt and Pfeiffer (1967) in 10-15 members of a kindred, and mesomelic dwarfism of the hypoplastic ulna, fibula and mandible type which is auto-soma1 recessive and probably represents homozygosity for dyschondrosteosis. Two new reports of this disorder were by Fryns and Vanden Berghe (1979), and by Kunze and Klemm (1980). Achondrogenesis 11, Grebe or Brazilian type, a severe type of dwarfism characterized by various bone aplasias and hypoplasias of the distal long bones of the limbs and hypoplastic digits, first detected and described in two German sisters by Grebe (1952), a new report of this disorder was by Khan and Khan (1982) in an Andhra family which belongs to a highly endogenous group in Pradesh, India.…”
mentioning
confidence: 92%
“…Léri-Weill syndrome (dyschondrosteosis) represents a short stature condition characterized by a symmetric shortening of the forearms and lower legs, and a bilateral shortening and bowing of the radius with a dorsal subluxation of the distal ulna (Madelung deformity) [10,11]. According to the clinical description, Langer's type of mesomelic dysplasia has been suggested to represent the homozygous form of Léri-Weill dyschondrosteosis [12][13][14]. Despite a prevalence of affected women [15], the syndrome was originally suggested to be inherited in an autosomal dominant manner.…”
Section: Shox In Léri-weill Syndromementioning
confidence: 99%
“…50 All patients with this syndrome have homozygous deficiency of the SHOX gene. 8,43 Fukami et al 37 summarized the clinical and molecular data on 17 patients with LMD reported so far.…”
Section: Langer Mesomelic Dysplasia (Lmd)mentioning
confidence: 99%